Effect of Foliar Spraying of Some Nutrients and Marine Algae Extract on Some Vegetative Growth Indicators of Apple Tree Golden Delicious Variety - كوسا تهاني; رشيد خربوتلي; عبد العزيز بوعيسى (Latakia University Journal -Biological Sciences Series, 2025)
The research was carried out in the province of Lattakia on an apple tree variety (Golden delicious)to find out the effect of foliar spraying with some nutrients in some of the vegetative growth qualities of apple trees, the research included spraying with potassium, boron, calcium and marine algae(algi firt top) individually or in combination with each other. Spraying with these materials led to the superiority of the studied treatments compared to the control, as the percentage of tree stem circumference increased significantly when spraying with a mixture of potassium, boron and marine algae extract10.27% For the average of the two years compared to the control 6.81%, the treatment of mixing potassium, boron and marine algae gave the highest percentage increase in the size of the tree crown relative to the average of the two years 14.11% and the lowest percentage of increase in the control treatment was 9.52%, and an increase was observed in the lengths of recent growths and all treatments outperformed the control 57.33 cm, while the highest value was in the treatment of boron, potassium and marine algae extract together, reaching in the average of the two years 64.77 cm. An increase in the paper area was also observed when spraying with these elements, which was 34.96 cm2 while the control was 24.96 cm2.